2011
DOI: 10.1080/17458080.2011.572085
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of supercooling of water by TiO2 nanoparticles as observed using differential scanning calorimeter

Abstract: Aqueous dispersions of Titania nanoparticles were cooled using differential scanning calorimetry (DSC). The nanoparticles reduce the supercooling of water by acceleration of nucleation. The experimental results demonstrated the important role in water crystallisation by the internal surface of the sample holder, and that stable nanofluids are required for the measurements to investigate the effect of nanoparticles on freezing. But for dispersions at low concentrations, such as 0.05 wt% and 0.1 wt%, the startin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 10 publications
1
16
0
Order By: Relevance
“…Wu et al (2009) investigated the cold storage performance of an Al 2 O 3 -H 2 O nanofluid and found that adding 0.2% Al 2 O 3 nanoparticles can shorten the crystallization time of the nanofluid by 20.5% and reduce its SD by 70.9% [8]. Mo et al (2013) and reported that TiO 2 nanoparticles can reduce the SD of water [9,15]. Kumaresan et al (2013) and discovered that scattered multiwalled carbon nanotubes in deionized water can serve as a nucleating agent to reduce the SD of water significantly [10,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wu et al (2009) investigated the cold storage performance of an Al 2 O 3 -H 2 O nanofluid and found that adding 0.2% Al 2 O 3 nanoparticles can shorten the crystallization time of the nanofluid by 20.5% and reduce its SD by 70.9% [8]. Mo et al (2013) and reported that TiO 2 nanoparticles can reduce the SD of water [9,15]. Kumaresan et al (2013) and discovered that scattered multiwalled carbon nanotubes in deionized water can serve as a nucleating agent to reduce the SD of water significantly [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have suggested the use of nanofluids as phase-change energy storage media [4][5][6][7][8][9][10][11][12][13][14]. As a common phasechange cold storage medium, water is environmentally friendly and cheap; however, water still has such limitations as high crystallization supercooling degree (SD) and relatively poor heat conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the presence of nanoparticles may also be able to perform as nuclei in addition to their primary functionality of enhancing the thermal conductivity of nanofluids. In the literature, the freezing point (supercooling degree), latent heat of crystallization, and crystallization kinetics of aqueous nanofluids have been characterized, both isothermally and non-isothermally, for a variety of metallic, metal oxide, and high aspect-ratio carbon nano-additives [27][28][29][30][31][32][33][34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…Nanoparticles like TiO 2 and Al 2 O 3 [88][89][90][91] are often added into PCMs to increase melting rate and reduce problems of refrigerating mediums such as environmental pollution, low thermal conductivity, large size and high installing and running cost. Hui et al [92] found that LiCl/H 2 O and NH 3 /H 2 O pairs have good performance among several absorbent/refrigerant pairs, which can be used for air conditioning application and subzero applications, respectively.…”
Section: Salt Hydrates For Air Conditioning Systemmentioning
confidence: 99%